Sickle cell disease in Uganda - Ndugwa, Christopher M (East African Medical Journal, 2003)
Objectives: To draw attention to the extent of homozygous sickle cell (SS) disease as a public health problem in Uganda where a mean 20% frequency of the sickle cell trait implies that 25,000 babies with SS disease are born each year. To highlight the dangers of applying interventions developed in non-malarial areas to regions where malaria may change the natural history and outcome of sickle cell disease. Data Sources: The published literature from Africa and from the US and Caribbean in populations of African ancestry. Study Selection: The world literature especially, that derived from the US, Caribbean, and equatorial Africa. Data Extraction and synthesis: In non-malarial areas, simple interventions applied early in life have significantly improved survival and the quality of life. Two well documented interventions are pneumococcal prophylaxis and the early parental diagnosis of acute splenic sequestration. The available literature from Africa suggests that neither of these may be appropriate in malarial areas. Conclusions: Manifestations of SS disease differ in malarial areas and it is questionable whether interventions developed in non-malarial areas apply. There is an urgent need to document the causes of death so that locally appropriate interventions may be developed to improve survival. Equally urgent is the need to define the pattern of clinical problems so that models of care may be evolved for use in malarial areas. Without this knowledge, health care planners will not have the information necessary to develop strategies and limited resources may be inappropriately deployed.
: a time for action
Keywords: Sickle cell disease; Uganda